The effects of drying temperature and duration on rose tea chemical and sensory profiles as a functional beverage - Bimo, Igoy Arya; Ali, Dego Yusa; Sunarharum, Wenny Bekti; Mu’awannah, Nailul; Athirah, Clarissa Evanarda; Jatmiko, Naila Syakira; Pranita, Meylda Dyah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study examined rose tea's stress-relieving potential through its chemical and sensory characteristics. Aligned with Indonesia’s SDG point 3, the phenolics and antioxidants contents of rose tea reinforce its role as a functional beverage. Variations in Oolong withering duration (18 hours), drying temperature (60°C and 80°C), and drying duration (1-3 hours) affected key properties, including acidity, sugar content, phenolics, flavor, aroma, and mouthfeel. Sensory and chemical analyses revealed that optimal drying conditions enhance taste and aroma, increased acidity and phenolics sharpen flavors, while higher sugar content balances the profile. Sample A1 (dried rose tea at 60°C for 1 hour) achieved the highest consumer acceptance due to its balanced acidity (0.19 ± 0.02 g/L), sweetness (14.00 ± 0.61 g/L), and floral aroma (3.49 ± 1.14). The phenolic content (1.21 ± 0.16 mg GAE/g) enhanced flavor without excessive bitterness (3.95 ± 1.25), while higher sugar content improved sweetness (3.84 ± 1.12). The well-balanced astringency (2.94 ± 1.41), floral flavor (3.81 ± 1.18), and sweet aroma (3.27 ± 1.37) contributed to its high preference, despite its lower brown (1.61 ± 0.81) and red (1.12 ± 0.42) color intensity. These findings highlight the importance of optimizing processing conditions to enhance both sensory appeal and functional benefits of rose tea.